Project Based Learning Modules to Improve Scientific Literacy and Problem-Solving Skill - Ardithayasa, I Wayan; Gading, I Ketut; Widiana, I Wayan (Universitas Pendidikan Ganesha, 2022)
This research was carried out due to the lack of use of varied teaching materials, causing a lack of scientific literacy and problem-solving skills of students in learning. This study aims to analyze the design, validity, practicality, and effectiveness of project-based learning-based modules to improve scientific literacy and problem solving in plant development materials. This research is development research using the 4D model (Four D Model). The subjects of this study were material experts, media experts, educators, and third grade elementary school students. Data collection methods used are interviews, documentation, and questionnaires. The type of instrument used is a closed questionnaire. Data collection techniques used are qualitative analysis techniques and quantitative analysis techniques. The results of this study indicate the results of the calculation of the effectiveness test on the overall scientific literacy ability using N-gain with a g value of = 0.74 with a high level of effectiveness. The results of the effectiveness test on overall problem-solving ability using N-gain obtained a g value of = 0.71 with a high level of effectiveness. Thus, the project-based learning module developed with the 4D model is valid, practical, and effective to be used as teaching materials. The implication of this research is that the project-based learning module developed is valid, feasible, and effective for use in learning.